Metode Asesmen Guru Dirosah terhadap Pengembangan Karakter Religius Siswa Sekolah Dasar Islam Terpadu Padang Islamic School - Sa’adah, Fuan; Sulaiman, Sulaiman (AS-SABIQUN, 2023)
This study aims to determine the assessment method carried out by dirosah teachers at the Padang Islamic School Integrated Islamic Elementary School through a qualitative method with a case study approach. Sources of data in this study were obtained through interviews, observation and data collection at school principals, Dirosah teachers, and homeroom teachers. Data analysis techniques used through analysis techniques from Miles and Huberman. The results of the study revealed first, that the teacher assessment plans were compiled based on a) determining learning objectives; b) identify the form of assessment carried out; c) create assessment instruments; d) implementation of the assessment; e) process the results of the assessment; f) present the results of the assessment in a report card. Second, in the implementation of teacher assessments, it is carried out with formative assessments and summative assessments. Third, the steps in conducting the teacher assessment are divided into seven, 1) observation; 2) tests used as material for consideration in the aspect of knowledge; 3) self assessment; 4) peer assessment; 5) interviews; 6) performance through the activities of students; 7) assignment, in this case it helps to raise back the value that has fallen.